Studi Meta-Analisis Transcranial Doppler Terhadap Glasgow Outcome Score Pada Cedera Otak Traumatik - William William; Rizal Tumewah; Denny Ngantung; Junita Maja Pertiwi; Melke Tumboimbela; Windy Mariane Virenia Wariki (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Traumatic brain injury (TBI) through primary and secondary brain injury causes ischemic, hypoxic, cerebral edema, increased intracranial pressure, which are related to physiological, emotional damage and disability. Transcranial Doppler (TCD) as a diagnostic tool can monitor increased intracranial pressure through hypoperfusion and also monitor vasospasm. This meta-analysis study aims to determine TCD as a diagnostic tool in predicting outcomes in TBI cases. Observational studies were taken on TCD examination in TBI cases. Clinical outcomes were assessed based on the Glasgow Outcome Score (GOS), Glasgow Outcome Score-Extended (GOS-E), and mortality. Secondary outcomes were the cut-off values of the Pulsatility Index (PI) and Lindegaard Ratio (LR) related to GOS, GOSE and mortality. Abnormal TCD values in TBI cases would have a 11 times greater likelihood of poor GOS (OR 11.51, 95% CI 7.75 to 17.10). Abnormal TCD had a 11 times greater likelihood of causing death compared to normal TCD (OR 11.05, 95% CI 5.99 to 20.40). Hypoperfusion on TCD had a 6 times greater likelihood of being associated with poor GOS (OR 6.33, 95% CI 0.28 to 144.48) and had a 22 times greater likelihood of causing death compared to vasospasm on TCD (OR 22.86, 95% CI 0.70 to 751.27). ROC curve analysis showed that the PI cut-off value of 1.03 and LR 3.3 were associated with poor GOS. TCD can be used as a diagnostic tool to predict poor GOS outcomes and mortality in TBI cases. Keywords: Transcranial Doppler, Glasgow Outcome Score, Traumatic Brain Injury ABSTRAK Cedera otak traumatik (COT) melalui cedera otak primer dan sekunder menyebabkan proses iskemik, hipoksik, edema serebral, kenaikan tekanan intrakranial, yang berkaitan dengan kerusakan fisiologis, emosional dan disabilitas. Transcranial Doppler (TCD) sebagai alat penunjang diagnostik dapat memantau kenaikan tekanan intrakranial melalui hipoperfusi dan juga memantau vasospasme. Studi meta-analisis ini bertujuan untuk menentukan TCD sebagai alat penunjang diagnostik dalam memprediksi luaran pada kasus COT. Studi observasional pemantauan TCD pada kasus COT diambil untuk dilakukan meta-analisis. Luaran klinis dinilai berdasarkan Glasgow Outcome Score (GOS), Glasgow Outcome Score-Extended (GOS-E), dan mortalitas. Luaran sekunder berupa nilai cut-off Pulsatility Index (PI) dan Lindegaard Ratio (LR) yang berhubungan dengan GOS, GOSE dan mortalitas. Nilai abnormal pada TCD akan memiliki kemungkinan 11 kali luaran GOS buruk (OR 11.51, 95% CI 7.75 to 17.10). TCD abnormal memiliki kemungkinan 11 kali menyebabkan kematian dibandingkan TCD normal (OR 11.05, 95% CI 5.99 to 20.40). Hipoperfusi pada TCD memiliki kemungkinan 6 kali berkaitan dengan GOS buruk (OR 6.33, 95% CI 0.28 to 144.48) dan memiliki kemungkinan 22 kali menyebabkan kematian dibandingkan vasospasme pada TCD (OR 22.86, 95% CI 0.70 to 751.27). Analisis kurva ROC memperlihatkan nilai cut-off PI 1.03 dan LR 3.3 berkaitan dengan GOS yang buruk. TCD dapat digunakan sebagai alat diagnostik untuk memprediksi luaran GOS buruk dan mortalitas pada kasus COT. Kata Kunci: Transcranial Doppler, Glasgow Outcome Score, Cedera Otak Traumatik